Acute Pancreatitis with Normal Serum Lipase: A Case Series - Shah, Anish M; Eddi, Rodney; Kothari, Shivangi T; Maksoud, Charbel; DiGiacomo, William Scott; Baddoura, Walid (JOP. Journal of the Pancreas, 2010)
Context Acute pancreatitis is diagnosed on the basis of clinical features, biochemical tests and imaging studies. Normal serum amylase level has been reported in the setting of acute pancreatitis but normal serum lipase level in acute pancreatitis is extremely rare. Case report Herein, we present a case series of acute pancreatitis with normal serum lipase levels along with a review of the topic. Conclusion In appropriate clinical setting, the diagnosis of acute pancreatitis should be entertained even with normal serum amylase and lipase levels. Image: MRI of the abdomen with contrast: prominent inflammatory changes surrounding the pancreas, with no necrosis or pseudocyst formation.